1999
DOI: 10.1055/s-1999-8840
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Complete Acromioclavicular Dislocation: Present Indications and Surgical Technique with Biodegradable Cords

Abstract: We report a retrospective study of 48 patients with complete acromioclavicular dislocation (Tossy III). All patients (38 male; 10 female) with an average age of 33.4 years underwent surgery including PDS-augmentation. More than half of the injuries were caused by sport accidents. There were no complications during surgery. 87% of the patients were free of complaints and subjectively very satisfied with the surgical results. By radiological examination we diagnosed a subluxation of the clavicula in 25% of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
1
9
0
1
Order By: Relevance
“…Removal of the coracoclavicular PDScords are not necessary. In several cases a rejection of PDS-cords leading to wound healing disorders were described [21]. In our study no complications related to the PDS-cord occurred.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Removal of the coracoclavicular PDScords are not necessary. In several cases a rejection of PDS-cords leading to wound healing disorders were described [21]. In our study no complications related to the PDS-cord occurred.…”
Section: Discussionsupporting
confidence: 51%
“…The anatomical gains of other surgical techniques varied with a loss of reduction in 20-40% of the cases [1]. As a result of isolated PDS-augmentation Moenig et al [21] diagnosed a subluxation in 25% and found arthrosis in 12% of the cases postoperatively. But by now the clinical relevance of radiological visible arthrosis remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,16) Recently, many authors recommend surgical reconstruction exclusively for young patients, in athletes or for heavy workers. 2,[28][29][30] In the current study, out of 77 cases, 8 cases (10%) were Rockwood classification type III. Although the authors chose conservative treatment for type III ACJ dislocations in most cases, operative treatment was indicated in patients with demands for greater functionality and early ROM.…”
Section: Discussionmentioning
confidence: 91%